Effect of a One-Week Spiritual Retreat on Brain Functional Connectivity: A Preliminary Study - Wintering, Nancy A. (Religions, 2021)
Background: Many individuals participate in spiritual retreats to enhance their sense of spirituality or to improve their overall mental and spiritual well-being. We are not aware of any studies specifically evaluating changes in functional connectivity using functional magnetic resonance imaging (fMRI) in individuals undergoing an intense spiritual retreat program. The goal of this study was to determine whether such changes occur as a result of participating in the Spiritual Exercises of St. Ignatius. Methods: We conducted psychological and spiritual measures in conjunction with functional connectivity analysis of fMRI in 14 individuals prior to and following shortly after their participation in a one-week spiritual retreat. Results: Significant changes in functional connectivity were observed after the retreat program, compared to baseline evaluation, particularly in the posterior cingulate cortex, pallidum, superior frontal lobe, superior parietal lobe, superior and inferior temporal lobe, and the cerebellum. Significant changes in a variety of psychological and spiritual measures were identified as result of participation in the retreat. Conclusion: Overall, these preliminary findings suggest that this intensive spiritual retreat resulted in significant changes in brain functional connectivity, and warrants further investigation to evaluate the physiological, psychological, and spiritual impact of these changes.